Integration of HIV and family planning services in sub-Saharan Africa: A review of the literature, current recommendations, and evidence from the service provision assessment health faculty surveys - Johnson, Kiersten; Varallyay, Ilona; Ametepi, Paul (DHS Analytical Studies No. 30, 2012)
This report provides a review of the current literature on integration of HIV-related services with other areas of service delivery that have important synergies with HIV services. The review indicates that while there remain concerns about integration, such as degradation of the quality of services, insufficient health system capacity, and financial implications, the balance of the literature finds that clinical, service delivery, cost-effectiveness, and rights-based benefits accrue from integration. This report also presents a descriptive analysis that uses national health facility survey data from the MEASURE DHS project‘s Service Provision Assessment (SPA) surveys to establish an HIV/FP service integration baseline in five countries in sub-Saharan Africa that have been hard-hit by the HIV epidemic: Kenya, Namibia, Rwanda, Tanzania, and Uganda. We highlight areas where integration can be strengthened in line with international recommendations and national policies, and provide recommendations for strengthening health facility survey data collection approaches to ensure optimal monitoring of HIV/FP service delivery integration in the future. Using data from the SPA‘s health worker interviews, facility inventories, and client-provider observations, we describe baseline levels of HIV- and FP-related service integration. This report documents considerable disparities between the availability of elements of integrated HIV/FP services, and the actual delivery by a health care provider of ANC or STI services that are fully integrated—where both HIV- and FP-related elements are actually incorporated into the visit.. This report also provides recommendations for adjustments to health facility survey questionnaires that would allow for more complete measurement of HIV/FP service delivery integration.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm. MEASURE DHS assists countries worldwide in the collection and use of data to monitor and evaluate population, health, and nutrition programs. Additional information about the MEASURE DHS project can be obtained by contacting MEASURE DHS, ICF International, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705 (telephone: 301-572-0200; fax:301-572-0999; e-mail: reports@measuredhs.com; internet: www.measuredhs.com)